Pengaruh Promosi Penjualan Buy Two Get One Free terhadap Keputusan Pembelian Produk Mie Sakera Jember - Rahmadi, Dedi; Neviyani, Neviyani; Wijaya, Shendy Andrie (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine the effect of the Buy Two Get One Free (B2G1F) sales promotion on consumers’ purchasing decisions for Mie Sakera, a local instant noodle brand from Jember. The research uses a quantitative associative approach with an explanatory design to examine the causal relationship between B2G1F promotion (X) and purchasing decision (Y). Data were collected from 35 respondents through questionnaires consisting of eight indicators for sales promotion and six indicators for purchasing decision. The results of the validity and reliability tests indicate that all items are valid and reliable, with Cronbach’s Alpha values of 0.608 (X) and 0.716 (Y). The normality test using Shapiro-Wilk shows that the data meet the normal distribution assumption, while the linearity test confirms a significant linear relationship between the two variables (Sig. Linearity = 0.001). The simple linear regression analysis produces a correlation coefficient (R) of 0.436 and a coefficient of determination (R²) of 0.190, meaning that 19% of purchasing decision variations can be explained by the B2G1F promotion. Furthermore, the regression equation Y = 44.958 + 0.483X with a t-value of 2.787 and Sig. = 0.009 (<0.05) indicates a significant positive effect of the promotion on purchasing decisions. Thus, the B2G1F strategy is proven effective in increasing consumer purchase intention and product attractiveness, suggesting that local brands like Mie Sakera can enhance competitiveness through promotional programs combined with consistent product quality and digital marketing efforts.